PENGARUH DISIPLIN KERJA, KEPUASAN KERJA DAN MOTIVASI KERJA TERHADAP PRODUKTIVITAS KARYAWAN DI WAROENG SPESIAL SAMBAL HERITAGE BOYOLALI - Wahyuni, Tri; Hegy Suryana, Alean Kistiani; Purwanto, Hari (EKOBIS, 2023)
This study aims to determine and analyze the effect of work discipline, job satisfaction and work motivation on employee productivity. This research is a quantitative research because the approach used for research proposals, the process of hypotheses, field work, data analysis, data conclusions up to writing uses aspects of calculation, formulas and certainty of numerical data. The subjects of this study were employees of the Boyolali Heritage Special Sambal. In this study, the population and sample were all employees at Waroeng Special Sambal Heritage Boyolali, totaling 49 people. Data analysis in this study used research methods using survey methods with research with information obtained directly from the head of the Boyolali Heritage Boyolali Special HR and from several of his staff. The results of the research analysis show that work discipline has a negative effect and there is no significance to employee productivity, job satisfaction has a positive but not significant effect on employee productivity and employee motivation has a positive but not significant effect on employee productivity. from this study it can be concluded that work discipline, job satisfaction and work motivation do not significantly influence employee productivity.